Seasonality of spatial patterns of abundance, biomass, and biodiversity in a demersal community of the NW Mediterranean Sea. (27th November 2019) - Vilas, Daniel; Pennino, Maria Grazia; Bellido, Jose Maria; Navarro, Joan; Palomera, Isabel; Coll, Marta
Abstract: Information on the spatial patterns and habitat preferences of marine species is key to understand the functioning of marine ecosystem and to manage and protect marine resources efficiently. However, the study of spatial patterns of marine ecosystems is challenging because they are dynamic environments that can vary seasonally. We modelled the spatial patterns of abundance, biomass, and biodiversity in a demersal community of the northwestern Mediterranean Sea by season using hierarchical Bayesian spatial models and environmental, physical, and anthropogenic factors. Overall, our findings revealed the importance of seasonality in the spatial patterns of the demersal community, which were mainly driven by sea surface temperature. Results also underlined important patterns of movements of demersal organisms: fishes, cephalopods, and crustaceans showed high densities in the area surrounding the Ebro Delta River in winter mainly driven by species-specific behaviour. Our results are relevant to inform future management measures in the study area, such as seasonal fishing restrictions, or to adapt local marine protected areas to seasonal processes. This study provides evidence of the need to expand current monitoring schemes to capture the seasonality of marine demersal communities for a more comprehensive marine spatial planning framework.